KREATIVITAS GURU AL-QUR’AN HADITS DALAM MENINGKATKAN MOTIVASI DAN HASIL BELAJAR PESERTA DIDIK DI MADRASAH IBTIDAIYAH NURUL FALAH MARGA TIGA KABUPATEN LAMPUNG TIMUR TAHUN PELAJARAN 2022/2023 - Nurhajah Alif (UNISAN JURNAL, 2024)
This research aims to evaluate the role of teacher creativity in enhancing student motivation and learning outcomes at Madrasah Ibtidaiyah Nurul Falah, Marga Tiga, Kabupaten Lampung Timur. The research method employed is a case study with a qualitative approach. Data were collected through observation, interviews, and document analysis. The findings indicate that teacher creativity significantly influences student motivation to learn. Teachers who utilize innovative teaching approaches are able to create an engaging learning environment that motivates students to actively participate. This also has a positive impact on student learning outcomes, with an improvement in understanding and application of Al-Qur’an and Hadith materials in daily life. Support from school principals, colleagues, and the school environment has also been proven to be crucial in enhancing teacher motivation and student learning outcomes. These findings have important implications for the development of teaching practices at Madrasah Ibtidaiyah Nurul Falah, Marga Tiga, and can serve as a guideline for other schools in enhancing the quality of Islamic education through the application of creativity in teaching Al-Qur’an and Hadith.